2011
DOI: 10.1371/journal.pone.0025572
|View full text |Cite
|
Sign up to set email alerts
|

Vision First? The Development of Primary Visual Cortical Networks Is More Rapid Than the Development of Primary Motor Networks in Humans

Abstract: The development of cortical functions and the capacity of the mature brain to learn are largely determined by the establishment and maintenance of neocortical networks. Here we address the human development of long-range connectivity in primary visual and motor cortices, using well-established behavioral measures - a Contour Integration test and a Finger-tapping task - that have been shown to be related to these specific primary areas, and the long-range neural connectivity within those. Possible confounding f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…We can conclude that the limitation of maximum motor speed in WS does not provide a full explanation of decreased speed in the serial task. In TD, both serial and index FT increase with age until adulthood (Gervan et al 2011); however, in WS performing a serial rather than a simple repetitive task puts a constraint on the speed of the performance. With respect to learning capacity, PR that is a combined measure of speed and accuracy Z-scores showed a decreased baseline coupled with similar or increased learning performance compared to the TD age group.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We can conclude that the limitation of maximum motor speed in WS does not provide a full explanation of decreased speed in the serial task. In TD, both serial and index FT increase with age until adulthood (Gervan et al 2011); however, in WS performing a serial rather than a simple repetitive task puts a constraint on the speed of the performance. With respect to learning capacity, PR that is a combined measure of speed and accuracy Z-scores showed a decreased baseline coupled with similar or increased learning performance compared to the TD age group.…”
Section: Discussionmentioning
confidence: 96%
“…We can conclude that the limitation of maximum motor speed in WS does not provide a full explanation of decreased speed in the serial task. In TD, both serial and index FT increase with age until adulthood (Gervan et al ); however, in WS performing a serial rather than a simple repetitive task puts a constraint on the speed of the performance.…”
Section: Discussionmentioning
confidence: 99%
“…Such delayed maturation for global visual processing is thought to be a consequence of restricted interactions between spatial cues at an earlier age (Kovács et al, 1999) as well as underdeveloped long-range connections (Gervan, Berencsi, & Kovács, 2011). Likewise, feedback and horizontal connections, which are useful for integrating contours, demonstrate delayed maturation (Lee, Birtles, Wattam-Bell, Atkinson, & Braddick, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent EEG-fMRI and MEG work (see Tanskanen et al, 2008; Mijovic et al, 2013) have confirmed the importance of early visual areas in the perception of contours, but also highlight the involvement of feedback from higher cortical areas such as the lateral occipital complex. Previous studies have shown that the processing of spatial contours (and perhaps the development of the abovementioned neural connections which might underpin contour grouping principles) is not optimal at birth, but rather follows a slow developmental perceptual process over a number of years (e.g., Kovacs et al, 1999; Gervan et al, 2011; Taylor et al, 2014). Interestingly, the contribution of closure and good-continuation to the detection of contours are dissociable and appear to be follow different stages of development (see Gerhardstein et al, 2004; Hipp et al, 2014).…”
Section: Introductionmentioning
confidence: 99%